Canine trypanosomiasis: Etiology of infection and implications for public health - Eloy, L. J. [UNESP]; Lucheis, Simone Baldini [UNESP] (FapUNIFESP (SciELO), 2009)
Canine trypanosomiasis, caused by protozoans of the genus Trypanosoma, is divided into two primary types: the American form (Chagas disease), due to Trypanosoma cruzi infection, and the African form (sleeping sickness or surra), provoked by Trypanosoma evansi. This disease was originally enzootic and affected only wild animals, including mammals and birds, which served as reservoirs. Later, it spread to domestic animals such as horses, cattle and dogs. The disease became a zoonosis when contact between rural inhabitants and natural Trypanosoma foci occurred, due to ecological imbalances and increasing migration. Dogs are significantly involved in this context, because they are the main domestic animals and participate in the transmission and maintenance cycles of these parasites. This article reports etiological, epidemiological and public health aspects of canine trypanosomiasis, and the most important peculiarities of this zoonosis in dogs.
Keywords: Canine trypanosomiasis; Chagas disease; Surra; Trypanosoma cruzi; Trypanosoma evansi